1999
DOI: 10.1128/aac.43.10.2451
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Absolute Bioavailability of Ribavirin in Healthy Volunteers as Determined by Stable-Isotope Methodology

Abstract: Ribavirin has recently been demonstrated to have efficacy in combination with alpha interferon for treatment of relapsed hepatitis C. The marked improvement in the response rate after treatment with the combination regimen (10-fold higher versus that from monotherapy with alpha interferon) highlights the importance of determining the absolute bioavailability of ribavirin as a first step in beginning to investigate the pharmacodynamics of the combination. The objective of this study was to determine the absolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
82
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(85 citation statements)
references
References 14 publications
1
82
1
1
Order By: Relevance
“…The dose and duration of oral ribavirin for the treatment of PIV3 pneumonia after HSCT have not been established. It is reported that the bioavailability of oral ribavirin is approximately 50% [20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…The dose and duration of oral ribavirin for the treatment of PIV3 pneumonia after HSCT have not been established. It is reported that the bioavailability of oral ribavirin is approximately 50% [20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacokinetic profile of ribavirin remained unchanged between patients with healthy livers and those with hepatic dysfunction, suggesting that the liver is not a major site of ribavirin metabolism [84]. Further, about 85% of the orally administered drug was found to be absorbed, although the absolute bioavailability of ribavirin is onlỹ 50% [86], which remains unchanged with hepatic dysfunction [84]. The gastrointestinal tract and not the liver thus appears to be the major site of first pass elimination [87].…”
Section: Pharmacokineticsmentioning
confidence: 91%
“…Thus, parameters that describe single-dose pharmacokinetics may not be applicable to the multiple-dose case. Preston et al [86] have employed two and three compartment models to fit experimental ribavirin plasma drug concentration profiles and find that the three compartment model provides a superior fit. However, what these compartments represent physically remains unclear.…”
Section: Pharmacokineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…A stable isotope study was planned with ribavirin in order to avoid the risk of insufficient washout between the treatment phases of a crossover design. To estimate absolute bioavailability, the study design involved IV administration of [ 13 C]-ribavirin followed 1 h later by an oral dose of unlabeled drug [18]. The use of stable isotope methodology provided a robust estimate of ribavirin bioavailability (51.8%) without a period bias or a washout effect to confound the data.…”
Section: Variability In Bioavailability Estimatesmentioning
confidence: 99%